Stem Cell-Like Properties of the Endometrial Side Population: Implication in Endometrial Regeneration - Masuda, Hirotaka (Public Library of Science, 2010)
BACKGROUND: The human endometrium undergoes cyclical regeneration throughout a woman's reproductive life. Ectopic implantation of endometrial cells through retrograde menstruation gives rise to endometriotic lesions which affect approximately 10% of reproductive-aged women. The high regenerative capacity of the human endometrium at eutopic and ectopic sites suggests the existence of stem/progenitor cells and a unique angiogenic system. The objective of this study was to isolate and characterize putative endometrial stem/progenitor cells and to address how they might be involved in the physiology of endometrium. METHODOLOGY/PRINCIPAL FINDINGS: We found that approximately 2% of the total cells obtained from human endometrium displayed a side population (SP) phenotype, as determined by flow cytometric analysis of Hoechst-stained cells. The endometrial SP (ESP) cells exhibited preferential expression of several endothelial cell markers compared to endometrial main population (EMP) cells. A medium specific for endothelial cell culture enabled ESP cells to proliferate and differentiate into various types of endometrial cells, including glandular epithelial, stromal and endothelial cells in vitro, whereas in the same medium, EMP cells differentiated only into stromal cells. Furthermore, ESP cells, but not EMP cells, reconstituted organized endometrial tissue with well-delineated glandular structures when transplanted under the kidney capsule of severely immunodeficient mice. Notably, ESP cells generated endothelial cells that migrated into the mouse kidney parenchyma and formed mature blood vessels. This potential for in vivo angiogenesis and endometrial cell regeneration was more prominent in the ESP fraction than in the EMP fraction, as the latter mainly gave rise to stromal cells in vivo. CONCLUSIONS/SIGNIFICANCE: These results indicate that putative endometrial stem cells are highly enriched in the ESP cells. These unique characteristics suggest that ESP cells might drive physiological endometrial regeneration and be involved in the pathogenesis of endometriosis.